Crosstalk between Two bZIP Signaling Pathways Orchestrates Salt-Induced Metabolic Reprogramming in Arabidopsis Roots. Issue 8 (14th August 2015) - Hartmann, Laura; Pedrotti, Lorenzo; Weiste, Christoph; Fekete, Agnes; Schierstaedt, Jasper; Göttler, Jasmin; Kempa, Stefan; Krischke, Markus; Dietrich, Katrin; Mueller, Martin J.; Vicente-Carbajosa, Jesus; Hanson, Johannes; et al.
Abstract : A signaling module in Arabidopsis roots, consisting of SnRK1 kinases and bZIP1 transcription factors, reprograms metabolism to enable plants to adapt to salt stress conditions. Abstract: Soil salinity increasingly causes crop losses worldwide. Although roots are the primary targets of salt stress, the signaling networks that facilitate metabolic reprogramming to induce stress tolerance are less understood than those in leaves. Here, a combination of transcriptomic and metabolic approaches was performed in salt-treated Arabidopsis thaliana roots, which revealed that the group S1 basic leucine zipper transcription factors bZIP1 and bZIP53 reprogram primary C- and N-metabolism. In particular, gluconeogenesis and amino acid catabolism are affected by these transcription factors. Importantly, bZIP1 expression reflects cellular stress and energy status in roots. In addition to the well-described abiotic stress response pathway initiated by the hormone abscisic acid (ABA ) and executed by SnRK2 (Snf1-RELATED-PROTEIN-KINASE2) and AREB-like bZIP factors, we identify a structurally related ABA -independent signaling module consisting of SnRK1s and S1 bZIPs. Crosstalk between these signaling pathways recruits particular bZIP factor combinations to establish at least four distinct gene expression patterns. Understanding this signaling network provides a framework for securing future crop productivity.